Faktor-Faktor Penyebab Masalah Disiplin di Sekolah - Arifin, Hasan (1998)
This study was conducted to determine the relationship between five factors as an independent variables with the discipline problem in the secondary school. Causes of the discipline problem in this research consist gender factors, individuals, family relationships, peer group and teachers. The objectives of this research is also to determine the factors itself, which are the most dominant influencing the causes of discipline problems in secondary school. Respondent consists secondary four from three schools in Marang district, Terengganu. There are 200 students have respond to the questionnaires. Six hypothesis are made for this research and examine using T-Test, Coleration Pearson Test, and Multiple Regression Test. The finding shows that there is no significant relationship between gender factor with the discipline problem in secondary school and there are significant relationship between individuals factors, family relationships, peer group and teachers with the discipline problem in secondary school. Peer group factors is the most dominant factor causes of the discipline problem in secondary school compared to individuals factors, family relationships, peer group and teachers.